Beyond inclusion: practical lessons on striving for gender and disability transformational changes in WASH systems in Cambodia and Timor-Leste. Issue 1 (17th January 2022) - Huggett, Chelsea; Da Costa Cruz, Livia; Goff, Fraser; Pheng, Pharozin; Ton, Doeurn
Abstract: Women and girls, and people with disabilities are often excluded from governance systems and decision-making on water, sanitation and hygiene (WASH) at all levels – from household to the national level. This paper analyses inclusion and empowerment outcomes for these two groups in three WASH system-strengthening programmes in Cambodia and Timor-Leste. The analysis used WaterAid's 'Equality and Inclusion Framework' to assess the quality of inclusion and empowerment outcomes at different levels of WASH systems. The review found that household gender equality changes in Timor-Leste were empowering because they shifted women's and men's roles, relationships and attitudes. It found that women's leadership and disability-inclusive approaches in Cambodia achieved inclusive outcomes because they enhanced women's critical consciousness and increased WASH leaders' awareness of the importance of disability inclusion. There was evidence of either individual/self-empowerment changes or changes to the enabling environment; however, no intervention achieved a comprehensive combination of both. The authors conclude that both individual and environmental outcomes contribute to empowerment outcomes in WASH systems at different levels that can shift gender norms, redistribute power and benefit women and people with disabilities. These findings will enable WASH practitioners to better understand empowerment outcomes and how to integrate them with system-strengthening approaches. HIGHLIGHTS: Gender equality and disability reduce inequalities in WASH system strengthening. Partnerships with women's rights groups and disabled people organisations. Practitioner perspectives from Cambodia and Timor-Leste. Testing field approaches and leveraging this learning to inform the influence of WASH systems nationally.